1999
DOI: 10.1093/emboj/18.5.1357
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in XPB and XPD helicases found in xeroderma pigmentosum patients impair the transcription function of TFIIH

Abstract: As part of TFIIH, XPB and XPD helicases have been shown to play a role in nucleotide excision repair (NER). Mutations in these subunits are associated with three genetic disorders: xeroderma pigmentosum (XP), Cockayne syndrome (CS) and trichothiodystrophy (TTD). The strong heterogeneous clinical features observed in these patients cannot be explained by defects in NER alone. We decided to look at the transcriptional activity of TFIIH from cell lines of XP individuals. We set up an immunopurification procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
156
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(162 citation statements)
references
References 36 publications
6
156
0
Order By: Relevance
“…These mutations are associated with loss of other functions such as transcriptional activity (41). A recent study suggests that perhaps a similar development has occurred with BACH1.…”
Section: Discussionmentioning
confidence: 93%
“…These mutations are associated with loss of other functions such as transcriptional activity (41). A recent study suggests that perhaps a similar development has occurred with BACH1.…”
Section: Discussionmentioning
confidence: 93%
“…We next addressed the role of ATP, which is required for the activity of the XPB and XPD helicases of TFIIH (33)(34)(35) in modulating the footprinting pattern of the damaged DNA around the lesion (36). We first observed that ATP does not modify the XPC/HR23B footprinting pattern of the damaged DNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The XPD gene encodes a helicase that is a component of the transcription factor TFIH. Mutations in the XPD gene can diminish the activity of TFIH complexes increasing the likelihood of repair defects, transcription defects and abnormal response to apoptosis (Sung et al, 1993;Coin et al, 1999). The low activity of repair defects may induce the progression of carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%